Extracellular α‐synuclein enters dopaminergic cells by modulating flotillin‐1–assisted dopamine transporter endocytosis. Issue 9 (18th June 2019) - Kobayashi, Junpei; Hasegawa, Takafumi; Sugeno, Naoto; Yoshida, Shun; Akiyama, Tetsuya; Fujimori, Koki; Hatakeyama, Hiroyasu; Miki, Yasuo; Tomiyama, Arata; Kawata, Yasushi; Fukuda, Mitsunori; Kawahata, Ichiro; et al.
ABSTRACT: The neuropathological hallmarks of Parkinson's disease (PD) include the appearance of α‐synuclein (α‐SYN)‐positive Lewy bodies (LBs) and the loss of catecholaminergic neurons. Thus, a potential mechanism promoting the uptake of extracellular α‐SYN may exist in susceptible neurons. Of the various differentially expressed proteins, we are interested in flotillin (FLOT)‐1 because this protein is highly expressed in the brainstem catecholaminergic neurons and is strikingly up‐regulated in PD brains. In this study, we found that extracellular monomeric and fibrillar α‐SYN can potentiate FLOT1–dopamine transporter (DAT) binding and pre‐endocytic clustering of DAT on the cell surface, thereby facilitating DAT endocytosis and down‐regulating its transporter activity. Moreover, we demonstrated that α‐SYN itself exploited the DAT endocytic process to enter dopaminergic neuron‐like cells, and both FLOT1 and DAT were found to be the components of LBs. Altogether, these findings revealed a novel role of extracellular α‐SYN on cellular trafficking of DAT and may provide a rationale for the cell type‐specific, functional, and pathologic alterations in PD.—Kobayashi, J., Hasegawa, T., Sugeno, N., Yoshida, S., Akiyama, T., Fujimori, K., Hatakeyama, H., Miki, Y., Tomiyama, A., Kawata, Y., Fukuda, M., Kawahata, I., Yamakuni, T., Ezura, M., Kikuchi, A., Baba, T., Takeda, A., Kanzaki, M., Wakabayashi, K., Okano, H., Aoki, M. Extracellular α‐synuclein enters dopaminergic cells by modulating flotillin‐1–assisted dopamine transporter endocytosis. FASEB J. 33, 10240–10256 (2019). www.fasebj.org